Sense of coherence as a protective factor of health related quality of life in Iranian older adults - Tahereh Komeili; Iman Khahan-Yazdi; Mohadeseh Sadri; Mahmoud Shokouhi-Tabar; Morteza Heidari; Zahra Taheri-Kharameh (Springer, 2024)
Abstract Sense of coherence supports human well-being by using internal and external resources to cope with stress and maintain health. The study was conducted in Qom, Iran from June to October 2022 explored the relationship between sense of coherence and quality of life in elderly Iranians. 300 older adults from a retirement center entered the study via the convenience sampling. Questionnaires of socio-demographic information, quality of life, and sense of coherence were used to collect and analyze the data. The analysis was done using descriptive statistics and multiple linear regression analysis. The majority of participants were male (77.3%) and married (88.7%), and they had a mean age of 64.4 (SD = 5.72) years. Comprehensibility (β = 0.15; P = 0.024), manageability (β = 0.19; P = 0.001), and meaningfulness (β = 0.20; P = 0.001) were associated with better quality of life after controlling for socio-demographic variables. The results indicated that the sense of coherence significantly predicts the quality of life among older adults. Future research should further investigate these findings in diverse populations and work towards developing effective interventions to enhance the quality of life of older adults.